An Intranasal Exposure Model of Lethal Nipah Virus Infection in African Green Monkeys. (30th October 2019) - Geisbert, Joan B; Borisevich, Viktoriya; Prasad, Abhishek N; Agans, Krystle N; Foster, Stephanie L; Deer, Daniel J; Cross, Robert W; Mire, Chad E; Geisbert, Thomas W; Fenton, Karla A
Abstract: Due to the difficulty in conducting clinical trials for vaccines and treatments against Nipah virus (NiV), licensure will likely require animal models, most importantly non-human primates (NHPs). The NHP models of infection have primarily relied on intratracheal instillation or small particle aerosolization of NiV. However, neither of these routes adequately models natural mucosal exposure to NiV. To develop a more natural NHP model, we challenged African green monkeys with the Bangladesh strain of NiV by the intranasal route using the laryngeal mask airway (LMA) mucosal atomization device (MAD). LMA MAD exposure resulted in uniformly lethal disease that accurately reflected the human condition.